Structural insights into transmembrane helix S0 facilitated RyR1 channel gating by Ca2+/ATP - Risheng Wei; Qiang Chen; Lei Zhang; Congcong Liu; Chuang Liu; Chang-Cheng Yin; Hongli Hu (Nature Communications, 2025)
Abstract The type-1 ryanodine receptor (RyR1) is an intracellular calcium release channel for skeletal muscle excitation-contraction coupling. Previous structural studies showed that the RyR1 activity is modulated by the exogenous regulators including caffeine, ryanodine, PCB-95 and diamide. An additional transmembrane helix, located adjacent to S1 and S4, has been observed in some structures, although its function remains unclear. Here, we report that using a mild purification procedure, this helix is co-purified with RyR1 and is designated as S0. When RyR1 is coupled with S0, it can be activated by Ca2+ to an open state; however when decoupled from S0, it remains in primed state. S0 regulates the channel conformation by directly affecting the TM domain via the pVSD-S0-S4/S5 linker coupling, which facilitates the dilation of S6. Our results demonstrate that S0 is an essential component of RyR1 and plays a key role in the physiological regulation of RyR1 channel gating.